Helium droplet infrared spectroscopy of glycine and glycine–water aggregates. Issue 40 (3rd October 2016) - Kaufmann, Matin; Leicht, Daniel; Schwan, Raffael; Mani, Devendra; Schwaab, Gerhard; Havenith, Martina
Abstract : Infrared absorption spectra of glycine and glycine–water aggregates embedded in superfluid helium nanodroplets were recorded in the frequency range 1000–1450 cm −1 . Abstract : Infrared absorption spectra of glycine and glycine–water aggregates embedded in superfluid helium nanodroplets were recorded in the frequency range 1000–1450 cm −1 . For glycine monomer, absorption bands were observed at 1106 cm −1, 1134 cm −1, and 1389 cm −1 . These bands were assigned to the C–OH stretch mode of the glycine conformers I, III and II, respectively. For glycine–water aggregates, we observed two bands at 1209 cm −1 and 1410 cm −1 which we assign to distinct conformers of glycine–H2 O. In all cases, the water is found to preferentially bind to the carboxyl group of the glycine.